PANDANGAN ALQURAN DAN HADIS TERHADAP SIFAT KIKIR (PELIT) - Hanif, Hanif (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2022)
This article aims to discuss the nature of miserliness in the view of the Koran and Hadith. This research uses descriptive analytical method with a qualitative approach within the scope of field research (Library Research). Allah denounces miserliness and asserts that his wealth surpasses all his creatures. Miserly among su'u al-adab (Bad Adab) to Allah which must be avoided because it violates Allah's commands and the breadth of His sustenance to humans. The Qur'an denounces and threatens miserly people, including: 1) Making his way into trouble easy, 2) His wealth will be hung around his neck on the Day of Resurrection, 3) People who are lulled by the tricks of Satan, 4) Characteristics of a hypocrite, 5) Characteristics of a wicked person. The hadith also discusses miserly behavior including: 1) The Prophet's prayer to be far from being stingy. 2) The prayer of destruction from the angel of god against the treasure of the miser that is stored. 3) Miserliness is the cause of the destruction of the former. 4) The miser is far from heaven and close to hell. 5) Miserly people are shunned by fellow humans. 6) Miserliness is a sign of imperfect faith. 7) A miser will not enter heaven. 8. Miserliness is the worst of traits. The Qur'an and hadith provide guidance so that humans are farthest from being stingy by realizing that wealth is an ornament of the world that Allah has entrusted to humans to spend properly because this treasure will be sucked away. So let people prepare for their suction in the hereafter.